High pre-pregnancy body mass index and gestational weight gain among women belonging to upper SES from Delhi, India - Priyanka Arora; Bani Tamber Aeri (Elsevier, 2023)
Background and objective: With increase in prevalence of obesity and an increasing trend in the birth of macrosomic infants, Institute of Medicine (IOM) guidelines pertaining to optimal gestational weight gain (GWG) required for positive pregnancy outcome were revised in 1990 and 2009. Since, in the Indian scenario, no recommendations exist for optimum GWG for obese (OB) and overweight (OW) women, we assessed the pattern of GWG w.r.t Institute of Medicine (IOM), 2009 among the subjects with different body mass index (BMI). Study design: Present data were a part of a longitudinal observational study wherein, 312 pregnant women (≤12th week of gestation) attending private antenatal clinics were followed till term and their weight was monitored regularly at pre-determined intervals i.e., 12th-14th, 18th-20th, 24th-26th, 30th-32nd, 36th + week of gestation and compared w.r.t IOM guidelines 2009. Results: 66.37 %, 57.89 % and 11.69 % of OB, OW and normal weight (NW) subjects respectively had weight gain exceeding their GWG limits. About 5 %,10.53 %, 33.77 % of OB, OW and NW subjects respectively had gained weight less than GWG limits (p = 0.000***). Conclusion: An increase in GWG inadequacy with increase in BMI and pronounced variations in GWG among OB and OW subjects underscore the necessity to monitor GWG especially among the subjects with high BMI.